Emotional Intelligence, Math Anxiety and Math Performance in Malaysia - Nur Fatihah, Mat Yusoff; Alber Bung, Chun Wei; Kartini, Abd Ghani; Goy, Siew Ching; Amalia, Madihie; Tan, Kock Wah (2022)
This study aims to investigate how Trait Emotional Intelligence (TEI) and mathematics anxiety could impact on math performance in a public university in Malaysia. A quantitative study with a specific cohort of Cognitive Science students comprising the 2nd and 3rd year students were carried out. More than 90% of the samples in the cohort were sampled. The questionnaire contained a component on demographic component, and sections on math anxiety (MARSSV) and Trait emotional intelligence questionnaires (TEIQue). The performance of the students in this study was measured by the mean score of math subjects. The result of the study showed that math performance was adversely related to math anxiety. However, Trait EI did not appear to influence math performance and neither did it have an impact on math anxiety. This finding is important as it suggests that more works need to be done to determine the leading predictor of math anxiety in the Malaysian context for subsequent effective intervention. This is among the very few study which explores the relationship between emotional self-efficacy using TEIQue, even though more than 2000 studies had been carried out using TEIQue (Trait Emotional Intelligence Questionaire).